DETECTION OF NEW HIV CASES UNDER EPIDEMIC CONTROL - WHEN IS IT THE RIGHT TIME TO REVIEW HIV TESTING ALGORITHMS FOR COUNTRIES NEARING THE 95-95-95 MILESTONES? CASE STUDY -BOTSWANA - Tapologo, Nkoane; Abubaker, Qutieshat (African Journal of Infectious Diseases, 2025)
Accurate diagnosis of human immunodeficiency virus (HIV) infection is dependent on using established national HIV testing algorithm. The purpose of this study was to review published articles to identify, and apply lessons learned to determine factors affecting transition of HIV testing algorithm for countries that have attained HIV epidemic control. We systematically searched peer-reviewed articles from online scientific databases; PubMed and Google Scholar from January 2019 to March 2024, using defined search phrases to extract articles. The defined search terms targeted articles focusing on issues of attained epidemic control and transitioning of HIV testing algorithm. Descriptive analysis was used to develop themes to answer the research question. The findings show that countries should consider the following areas before changing their HIV testing algorithm: (i) evaluate the current national HIV testing algorithm to determine the Positive Predictive Value (PPV), which should be ≥ 99%, (ii) evaluate test kits bearing both CE and FDA certification and are WHO pre-qualified (iii) 4 generation Rapid Diagnostic Tests (RDTs) are less sensitive than laboratory-based 4 generation assays, (iv) pilot the proposed algorithm before country-wide roll-out, (v) country specific policies, and framework are required to guide transition, and (vi) a combination of 4 and 3 generation RDTs can achieve desired PPV. Transitioning HIV testing algorithm for countries reaching HIV epidemic control is a multistep process which considers the PPV of the current algorithms, considers policies and framework to guide the process and, evaluates a combination of 4 and 3 generation RDTs.